Friction characteristics of post-tensioning tendons in full-scale structures - Kim, Sang Hyun; Park, Sung Yong; Park, Young Hwan; Jeon, Se Jin (Engineering Structures, 2019)
Friction characteristics between the strands and the duct have a significant effect on the distribution of prestressing force and can be incorporated by the curvature and wobble friction coefficients in the design of prestressed concrete structures. However, the recommended friction coefficients show a wide range of variation, which can cause the inaccurate estimation of prestressing force. In this study, the friction coefficients were evaluated based on the strains of tendons measured by Smart Strands using optical fiber sensors in a full-scale test specimen and two actual long-span girder bridges. The test specimen was investigated to determine how the duct shapes and other factors affect the friction coefficients. Simultaneous equations method and least squares method for obtaining friction coefficients were employed and the results were compared in the actual bridges. This study shows one of the applications of the developed Smart Strand system that can overcome several drawbacks of the existing measurement system.
Keywords: Friction characteristics; Friction coefficients; Full-scale structures; Least squares methods; Prestressing tendon; Sheath; Simultaneous equations; Strand; Duct; Fiber Bragg grating; Friction coefficient; Optical fiber sensor; Prestressed concrete structure; Prestressing tendon; Sheath; Strand